2011
DOI: 10.5539/jas.v4n3p227
|View full text |Cite
|
Sign up to set email alerts
|

SRAP Markers and Morphological Traits Could Be Used in Test of Distinctiveness, Uniformity, and Stability (DUS) of Lettuce (Lactuca sativa) Varieties

Abstract: The test of distinctiveness, uniformity, and stability (DUS) is a necessary step for variety identification and new variety application. The objective of this study is to provide molecular marker-assisted approach combined with morphological trait-based testing for more convenient and fast DUS test and identification of varieties. Eighteen pairs of SRAP markers and 40 morphological traits for DUS test were applied for genetic diversity analysis of 50 lettuce (Lactuca sativa) varieties. Average polymorphism inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Furthermore, morphological traits capture only a small portion of allelic variation, whereas SRAP analysis provides a more extensive coverage of the genome (Al-Faifi et al, 2013). Our results are in agreement with previous studies that reported moderate or low correlation between the morphological traits and SRAP analysis (Fufa et al, 2005;Liu et al, 2012).…”
Section: Correlation and Comparison Between Srap Markers And Morpholosupporting
confidence: 95%
“…Furthermore, morphological traits capture only a small portion of allelic variation, whereas SRAP analysis provides a more extensive coverage of the genome (Al-Faifi et al, 2013). Our results are in agreement with previous studies that reported moderate or low correlation between the morphological traits and SRAP analysis (Fufa et al, 2005;Liu et al, 2012).…”
Section: Correlation and Comparison Between Srap Markers And Morpholosupporting
confidence: 95%
“…The effectiveness and accuracy of any distinctness assessment relies on the existence of a comprehensive and accurate database of commonly known varieties. The currently available database is based on the morphological characterization of commonly known varieties, which, although accurate and scientifically robust, also has several limitations, being slow, expensive, resource intensive, and time-consuming ( Liu et al., 2012 ). In addition, as morphological characteristics are easily affected by environmental factors, such as temperature, light, and fertilizer application, and data collected in different ecological places or in different seasons may be quite different, which may cause errors when screening for similar varieties using the distinctness test.…”
Section: Introductionmentioning
confidence: 99%